Behaviour of Synthetic Polymer-Modified Warm Mix Asphalt Under Oven Ageing Simulation - Daniel, Christian Gerald; Widjajakusuma, Jack; Setiawan, Erik S. (Journal of Civil Engineering, 2023)
This research evaluates the mechanical properties and fracture behaviour of ethylene-vinyl acetate (EVA) polymer-modified warm mix asphalt under the influence of ageing simulated through oven heating at 85oC in two different durations of 2 and 8 days. EVA contents of 4 - 6% of binder weight were employed, and the effect was measured through the semi-circular bending (SCB) test. Volumetric properties measurement showed negligible effect of polymer addition, with the difference in air void ratio ranging from 0.5% to 8% compared to the control mix. Meanwhile, the density and void in mineral aggregate (VMA) differed by a maximum of 2% compared with the control mixture. Moreover, the increase in the heating period was found to enhance the tensile strength, with a maximum difference of 81.72% exhibited by the mix with 0.5% EVA, corresponding to its tensile strength from the 8-day ageing conditioning by 28% larger than the control mix. Moreover, crack resistance and flexibility indexes (CRI and FI) were inversely proportional to the increase of polymer dosages for both 2- and 8-day aged specimens from being 20.5% and 52% to 6.4% and 18.3% larger than the control mixture, respectively, with the 8-day aged specimens having the CRI of 8% larger and FI of 8.7% smaller than the 2-day aged samples, indicating a brittle behaviour in respect to the ageing duration. Conclusively, the heating ageing simulation results in a brittle asphaltic mixture modified with EVA, displayed with higher strength and lower flexibility, particularly at 5% to 6% w/t.